TRUST AND PERCEIVED BENEFIT AS ANTECEDENTS OF REUSE INTENTION IN MOBILE PAYMENT SERVICES - Narahdita, Ajeng Putri; Aisjah, Siti; Kusniyah, Nur (Universitas Brawijaya, Indonesia, 2020)
The purpose of this study is to describe and analyze the direct and indirect relations between trust, perceived benefit, perceived risk, and reuse intention. The population of this research is to graduate students who have used Go-pay. Using a purposive sampling method with a nonprobability sampling technique, 177 people were selected as respondents. Research findings show that the trust had an influence directly against the perceived benefit, perceived risk, and reuse intention. Furthermore, the perceived benefit directly influence reuse intention. Besides, this research confirmed that the perceived benefits partially mediate the relationship of trust in the intention of reuse. Nevertheless, the perceived risk does not influence reuse intention.